Arvin's Realistic Personality Development in Donald Ray Pollock’s The Devil All the Time - Utomo, Mochammad Ibnu Prasetyo; Nurhadi, Muizzu; Jatmiko, Dheny (Cultural Narratives, 2023)
The purpose of this research is to analyse the personality development and the factors that influence the personality development of Arvin, in The Devil All the Time by Donald Ray Pollock. The researcher sets three formulations of the problem to be analysed the first is identifying Arvin’s basic personality. The second is identifying Arvin's personality development. Third is identifying the factors that cause Arvin's personality development. To analyze the formulation of the problem, the researcher uses character theory and characterization to identify Arvin's basic personality, then uses Elizabeth B. Hurlock's personality development theory to identify personality development and the factors that influence Arvin's personality development. The results of this study found that the first is Arvin's basic personality, namely innocent child, obeying his father's orders, and having strong faith. Second is Arvin's personality development, namely from an innocent child to a skeptical mind, from a faithfulness child to a rebellious child, and from having strong faith to losing faith. Third, factors that influence Arvin's development are physical changes, changes in the family, changes in the environment, and significant people. However, from the four personality development factors that the researcher found, significant people have the most influence on Arvin's personality development. The conclusion is that Arvin experienced personality development from a good child to a realistic and rude child, this factor was caused by a significant person, namely his father.